Re/searchers as Co-learners: Life Narratives on Collaborative Re/search in Aboriginal Communities - Heather Castleden; Denise Kurszewski (Adult Education Research Conference, 2000)
Our goal is to share our lived experience of the unanticipated learning that occurred during our inquiry into educational issues in Aboriginal communities. What stems from this inquiry is a recognition that re/searchers are co-learners rather than experts. Consequently, we are endeavouring to increase awareness of ethical considerations regarding re/search.